PENGEMBANGAN E-MODUL DESAIN GRAFIS PERCETAKAN BERBASIS DUNIA INDUSTRI DI SMK NEGERI 1 SELAYAR - Muhammad Jefri; Hasanah Nur; Anas Arfandi (Universitas Negeri Makassar, 2023)
This study aims to develop learning media in the form of an Industrial World-Based Printing Graphic Design E-Module at SMK Negeri 1 Selayar. The type of research that the author uses is Research and Development (R&D). Using the 4D development model (Define, Design, Develop, and Disseminate). Which is modified into a 3D model (Define, Design, and Develop). The results of this study indicate that the learning media in the form of Industrial-based Printing Graphic Design E-Module is appropriate for use in teaching and learning by teachers and students. Based on several stages of trials, the learning obtained was valid with the eligibility level of the validity test with the results of media expert I of 94.2% and media expert II of (81.7%) with a very valid category, the author's practice test obtained results on material expert I of (96.8%), on material expert II of (95.3%) and on the test of 20 training students (93.7%) with a very practical category, based on the results of this product test, it can be useful for teachers, students and advanced students